1987
DOI: 10.1139/e87-078
|View full text |Cite
|
Sign up to set email alerts
|

Directional orientations of solitary rugose corals

Abstract: Unattached solitary rugose corals lying parallel to bedding are common in many Ordovician and younger Paleozoic units, but their directional orientations have seldom been examined. Interpretations based on occurrences in North American Upper Ordovician and Lower Silurian strata provide a foundation for such studies. Distinct directional patterns resulted from preferred orientation with respect to water motion. They indicate transportation rather than biologic orientation, if it can be shown that the corals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The fact that we demonstrated here that Manicina coralla can 'flip over' while being oriented parallel to the current, rather than just being rolled perpendicular to the current may have some important considerations for paleoenvironmental reconstruction in muddy environments using similarly shaped rugosans (ELLAS 1984, ELLAS et al 1987, ELLAS et al 1988, BOLTON & DRIESE 1991. It has been claimed that orientation of horn-shaped corals would be preferentially perpendicular to the prevailing currents, since coralla would primarily be rolled.…”
Section: Discussionmentioning
confidence: 86%
“…The fact that we demonstrated here that Manicina coralla can 'flip over' while being oriented parallel to the current, rather than just being rolled perpendicular to the current may have some important considerations for paleoenvironmental reconstruction in muddy environments using similarly shaped rugosans (ELLAS 1984, ELLAS et al 1987, ELLAS et al 1988, BOLTON & DRIESE 1991. It has been claimed that orientation of horn-shaped corals would be preferentially perpendicular to the prevailing currents, since coralla would primarily be rolled.…”
Section: Discussionmentioning
confidence: 86%
“…based on the morphology of a cardinal septum, generally an ar rangement of thickened septa around the cardinal plane or devel opment of a cardinal fossula where the septum is short. Elias (1984) and Elias et al (1988) indicated that, in several Ordovician genera, the cardinal area is oriented in the downcurrent direction and occurs on the convex side of the corallum, so that the plane of corallum bilaterality is vertically oriented. No such preferred orientation of bilateral corals has been determined for H. halli; however, specimens here reported were not collected in situ.…”
Section: External Morphology Of Heliophyllum Halumentioning
confidence: 99%
“…A coral with a straight growth axis and growth lines perpen dicular to it apparently lived partially or largely buried in sub strate, with the rim of the calice situated at some viable distance above a soft substrate (Hubbard, 1970;Elias, 1984;Elias and Buttler, 1986;Elias et al, 1988;Neuman, 1988). Fedorowski (1997, p. 30) stated that it is proven that Caninia lived in a per pendicular position, based on examination of in situ specimens and on growth lines in this Carboniferous genus.…”
Section: External Morphology Of Heliophyllum Halumentioning
confidence: 99%
See 2 more Smart Citations